Evil, Privation, Depression and Dread - Robson, Mark Ian Thomas (New blackfriars, 2013)
In this essay I examine the idea that evil is to be understood as a kind of absence or a privation. I put forward two arguments against this idea. The first claims that if evil is an absence it becomes causally powerless, which seems strongly contradicted by experience and revelation. The other argument says that the idea that evil is an absence cannot do justice to the evil of depression. Depression is a set of feelings which are all too real, and so cannot be understood as literally identical with a set of absences.